HEATHCLIFF’S SELF ACTUALIZATION IN WUTHERING HEIGHTS BY EMILY BRONTE - Ririn Fatmawati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2019)
This research discusses about Heathcliff’s Self-Actualization in Wuthering Heights written by Emily Bronte which is set in the Yorkshire moors of Northern England. The inductive method is used to make the discussion of the topic brief. It means that the analysis starts from the specific concept goes to general conclusion. The data used in this thesis are collected by library research. This article also applies Maslow’s Hierarchical Theory of motivation. There are five hierarchies of needs which have to be fulfilled before someone goes through to accomplish self actualization, those are physiological needs, safety needs, belongingness and love needs and the last needs are self-esteem needs. This article focuses on how Heathcliff fulfil his psychological need, how he get his safety need, how he get the belongingness and love need, how he reach his self-actualization. . The research is to find Heathcliff succeeded to complete his self actualization in Wuthering Heights. Heathcliff can achieve his self-actualization because he wants to become a total kind of person to reach his dream whatever way he has done. He is able to unify Wuthering Heights and Thrushcross Grange, and making Hareton as slave.